Pelatihan Pembuatan Selai dari Kulit Kopi sebagai Upaya Peningkatan Nilai Tambah dan Ide Wirausaha di Desa Pamriyan - Zainal Abidin; Sapto Nugroho; Asih Wulan Sari; Tsania Royani Abdillah; Malikhatul Hasanah; Yustika Trisiana Agun; Ridi Arif (Institut Pertanian Bogor, 2022)
Coffee is a superior commodity owned by Indonesia. One of the coffee producing areas in Central Java is in Pamriyan Village, Pituruh Subdistrict, Purworejo Regency with an area of 1009.75 ha. The high production of coffee produced is also followed by the high waste of coffee produced which is not currently utilized properly. On the other hand, the coffee rind has the potential as a food rich in antioxidants such as polyphenols, anthocyanins, tannins, plavanols, 3-ol flavans, hydroxionic acids, and kafrin. This activity aims to provide an overview of the potential of resources that can be developed in Pamriyan Village and provide insight into the added value of coffee waste as well as entrepreneurial ideas to improve the economy of pamriyan villagers. The activity was carried out with material delivery and direct practice of making Coffee Skin Jam (SEKUPI). In this SEKUPI practice activity, it was obtained that almost all participants liked the taste, texture, and packaging of coffee skin jam and all participants agreed that this product was worth selling and developing. Analysis of the calculation of the cost of production was obtained that each manufacture of 10 bottles of SEKUPI will produce a profit of Rp 66,300,00. Furthermore, the calculation of R/C value is obtained a result of 1.203 which means that the business provides profits and is worth developing. Trainees are very happy with this training activity because it has added to their insights and gained new business opportunity ideas to develop in Pamriyan Village.